A study on assessment of mass drug administration for elimination of lymphatic filariasis in Datia district, Madhya Pradesh - Gupta, Ginisha; Marskole, Priyesh; Yuwane, Praveen (International Journal Of Community Medicine And Public Health, 2018)
Background: Currently 947 million people globally live in areas having endemic lymphatic filariasis and require preventive chemotherapy to stop the spread of infection. LF is transmitted by many mosquitoes particularly Culex and in some areas by Anopheles and Aedes too. This study was conducted to assess the programme implementation with respect to process and outcome indicators and to assess the reasons for non-compliance among population. Methods: We conducted a cross sectional study in Datia district, Madhya Pradesh during September 2014. We determined the sample size for survey based on standard guidelines for MDA coverage assessment. We identified four separate clusters, each with thirty households, for the survey. We selected three clusters from rural areas and one cluster from urban area to ensure adequate representation. We used stratified sampling technique for selection of three rural clusters. Results: We surveyed 859 study participants of Indergarh block, Datia district, residing in 120 households across four clusters. Among 859 study participants, the eligible population (excluding less than two year child and pregnant females) was 92% (790/859). District health authorities reported coverage of MDA across entire district to be 91%. We determined the distribution rate of DEC across all four clusters to be 84% (±9%). We identified highest drug distribution rate in Uchad (97%; 193/200) and lowest in Bargai (75%; 133/178). Conclusions: Non-compliant individuals are potential reservoir for the parasite which may serve as source of infection and transmission even after the mass drug administration ceases. As the prevalence of lymphatic filariasis continues to decrease with the implementation of control measures, addressing the issue of non-compliance holds primary importance to further substantiate the effect of our efforts.